Comparison of Predictive Models for Photovoltaic Module Performance under Tropical Climate - Koumi Ngoh Simon; Njomo Donatien; Moungnutou Mfetoum Inoussah (Universitas Ahmad Dahlan, 2012)
This paper examines four models which are used to estimate the performance of photovoltaic (PV) modules when the irradiances and PV cell temperatures are known. The models were simulated and the operating temperature and irradiance dependence of PV electrical efficiency and power output were studied. The models accuracy was obtained by comparing the models and the measurements of maximum power for a polycrystalline typical MXS 60 PV module under tropical climate. The evaluated models for estimating the maximum power are the single diode, the Photovoltaic geographical information system (PVGIS), the Borowy and Salameh, and the Hatziargyriou model. The analysis of the error curves shows that the single diode and Hatziargyriou model have better accuracy. The PVGIS and Borowy approach are not appropriate as the module performance prediction in Sudanese sahelian climate.